Diet of invasive wild pigs in a landscape dominated by sugar cane plantations - Pedrosa, Felipe [UNESP]; Bercê, William [UNESP]; Costa, Vladimir Eliodoro [UNESP]; Levi, Taal; Galetti, Mauro [UNESP] (Oxford University Press (OUP), 2021)
Understanding the mechanisms by which alien species become invasive can assure successful control programs and mitigate alien species' impacts. The distribution of invasive wild pigs (Sus scrofa) has been sharply expanding throughout all regions of Brazil in the last few years. Here we demonstrate that large monocultural plantations provide the primary resource subsidies to invasive wild pigs in Brazil. We analyzed 106 stomach contents and carbon stable isotopes (δ13C) of 50 hair samples of wild pigs from a population immersed in a landscape dominated by sugar cane agriculture. Stomach contents were dominated by corn (41%), sugarcane (28.5%), vegetal matter (all other vegetation besides crops, 27%), and animal matter (vertebrates and invertebrates, 4%). Bayesian mixing model analysis of δ13C showed that food sources from C4 photosynthetic pathway (represented by corn and sugarcane) accounted for 94% of the long-term diet, while C3 food sources for only 6.2%. Our results indicate that corn and sugar cane are subsidizing the diet of wild pigs and can facilitate the population growth of this invasive species. Given that Brazil is a major agricultural producer and a hotspot of biodiversity, it is extremely concerning that extensive agriculture may accelerate the expansion of this invasive species, resulting in economic losses and cascading effects on natural habitats.
Keywords: alien species; Atlantic Forest; caça; espécies invasoras; feral swine; forest fragmentation; fragmentação florestal; javaporco; Mata Atlântica; wild boar